Buddhism and International Humanitarian Law - Bartles-Smith, Andrew; Crosby, Kate; Harvey, Peter; Tilakaratne, Asanga; Ratheiser, Daniel; Maurer Trew, Noel; Travagnin, Stefania; Harris, Elizabeth J.; Deegalle, Mahinda; Kilby, Christina A. (Taylor & Francis, 2024)
What guidance can Buddhism provide to those involved in armed conflict and to belligerents who must perhaps kill or be killed or defend their families, communities or countries from attack? How, moreover, does Buddhism compare with international humanitarian law (IHL) - otherwise known as the law of armed conflict - which protects non-combatants and restricts the means and methods of warfare to limit the suffering it causes? Despite the prevalence of armed conflict in parts of the Buddhist world, few contemporary studies have addressed these questions. While there is a wealth of material on Buddhist conflict prevention and resolution, remarkably little attention has been paid to what Buddhism says about the actual conduct of war. IHL is also still relatively little known in the Buddhist world and might not therefore influence the behaviour of belligerents who self-identify as Buddhists and are perhaps more likely to be guided by Buddhist principles. This ground-breaking volume is part of an International Committee of the Red Cross project which seeks to fill this gap by exploring correspondences between Buddhist and IHL principles, and by identifying Buddhist resources to improve compliance with IHL and equivalent Buddhist or humanitarian norms. This book will be of much interest to students and researchers of International Law, Buddhism, Ethics as well as War and Conflict studies. The chapters in this book were originally published as a special issue of Contemporary Buddhism.